Propuesta urbano-arquitectónica de un equipamiento público de uso mixto como elemento de transición a la movilidad sostenible centro histórico de la ciudad de Ibarra, Ecuador - Guevara Guevara, Emerson Alexander (2024)
This thesis focuses on improving the mobility of the Historic Center of the city of Ibarra, Imbabura, Ecuador, under the proposal of a mixed-use public facility, which will function as a transition element to sustainable mobility, in this place it will be carried out some investigation, planification and mobility ordering activities, in relation to the comunity. The design process is proposed, through analyzes carried out on site and participatory methods, corresponding to pedestrian, cycling and vehicular flows, in order to understand the current way of mobility and the relationship that exists with economic and cultural activity. In addition, the existing pedestrian environments are evaluated on a microscale, with the aim of understanding the walkability index presented by the streets of the historic center of Ibarra. This thesis seeks to provide an answer to the question of\; How to generate a transition to sustainable mobility? which arises from the existing mobility problems in a historical environment. It concludes with the answer to the question posed, with the design of a facility and its immediate urban environment, through the design of mobility research spaces and the design of streets and intersections focused on active mobility.